Report on houseless poor, other than destitute wayfarers and wanderers - Pim, Jonathan (Statistical and Social Inquiry Society of Ireland, 1876)
Taking the houseless poor, recorded amongst the admissions to the Bow-street Night Asylum as ?strangers?, to represent the wayfarers and wanderers, and those recorded as ?citizens? to represent the other houseless poor, the Committee find in the statistics of 1874, the number of wayfarers and wanderers, 49 each night; and the number of other houseless poor, 121. The aggregate admissions of the first class (wayfarers, etc.) amounts to 17,880 in the year, and of others to 44,781. In the latter number there is, most probably, a much larger proportion of re-admissions, making the number of distinct individuals of each class relieved throughout the year more nearly equal than the total admissions in the year, or the average number each night would indicate. The committee of the asylum are taking steps towards distinguishing the number of distinct individuals amongst such total number of admissions.
Read before the Society, 18 April 1876
Keywords: Statistical and Social Inquiry Society of Ireland; Charity Organisation Committee; Housing need; Homelessness; 314.15